Association between elite swimmers` force production and 100 m front crawl inter-lap pacing and kinematics - Costa, M. J.; Santos, C. C.; Ferreira, F.; Arellano, R.; Vilas-Boas, J. P.; Fernandes, R. J. (Frontiers in Sports and Active Living, 2023)
The present study aimed to analyse the associations between force production and 100 m front crawl inter-lap pacing and kinematics. Eleven elite male swimmers performed a 100 m front crawl maximal effort to collect 50 m lap time (T50, s) and velocity (v, m·s-1) for pacing, stroke rate (SR), stroke length (SL) and stroke index (SI) as kinematic variables. A 30 s tethered effort allowed to determine the peak (Fpeak) and mean force (Fmean) as force production variables. The relative change (delta) between 50 m laps was also calculated for all measures. A paired sample t-test was used to check differences between laps and Pearson correlation coefficients allowed to quantify the associations between force and remaining variables. The T50 increased from the first to the second lap (deltaT50 = 10.61%, p < 0.01, d = 2.68), while v (deltav = -5.92%, p < 0.01, d = 1.53), SR (deltaSR = -6.61%, p < 0.01, d = 0.45) and SI (deltaSI = -4.92%, p = 0.02, d = 0.45) decreased. SL remained unchanged between laps (deltaSL = 1.07%, p = 0.66, d = 0.08). No associations were found between force production and most of delta, with the only exception being the reasonable good association between Fpeak and deltav (r = 0.62, p = 0.04). Although both pacing and kinematics fall from the first to the second sections of a 100 m front-crawl effort, the swimmers who exhibit higher Fpeak show a more stable front crawl v between both 50 m laps.